An Evaluation of the Use of Seasonal Goal Lines to Improve the Accuracy of Curriculum-Based Measurement of Reading Decision Rule Recommendations. (June 2021) - Van Norman, Ethan R.; Nelson, Peter M.
The current study evaluated whether goal-setting practices that account for seasonal developmental patterns of reading growth decreased the number of weeks data needed to be collected in order to yield accurate response to intervention decisions for a sample of 224 third-grade students. The extent to which more complex decision-making practices improve upon the accuracy of current frameworks across periods of 4 to 8 weeks was also explored. Spring proficiency status on a curriculum-based measurement of reading assessment was used as the reference for classification accuracy. Using a goal line based upon fall to winter grade-level benchmarks tended to produce higher levels of accuracy, kappa, and sensitivity than goal lines based upon fall to spring benchmarks. Collectively, the observed results highlight the potential benefit of establishing seasonal goal lines and suggest that relatively simplistic and accessible approaches to decision-making may result in similar decisions when compared with analytically complex approaches.